Characteristics of COVID‐19 patients with bacterial coinfection admitted to the hospital from the emergency department in a large regional healthcare system. Issue 5 (12th February 2021) - Lardaro, Thomas; Wang, Alfred Z.; Bucca, Antonino; Croft, Alexander; Glober, Nancy; Holt, Daniel B.; Musey, Paul I.; Peterson, Kelli D.; Trigonis, Russell A.; Schaffer, Jason T.; Hunter, Benton R.
Abstract: Introduction: The rate of bacterial coinfection with SARS‐CoV‐2 is poorly defined. The decision to administer antibiotics early in the course of SARS‐CoV‐2 infection depends on the likelihood of bacterial coinfection. Methods: We performed a retrospective chart review of all patients admitted through the emergency department with confirmed SARS‐CoV‐2 infection over a 6‐week period in a large healthcare system in the United States. Blood and respiratory culture results were abstracted and adjudicated by multiple authors. The primary outcome was the rate of bacteremia. We secondarily looked to define clinical or laboratory features associated with bacteremia. Results: There were 542 patients admitted with confirmed SARS‐CoV‐2 infection, with an average age of 62.8 years. Of these, 395 had blood cultures performed upon admission, with six true positive results (1.1% of the total population). An additional 14 patients had positive respiratory cultures treated as true pathogens in the first 72 h. Low blood pressure and elevated white blood cell count, neutrophil count, blood urea nitrogen, and lactate were statistically significantly associated with bacteremia. Clinical outcomes were not statistically significantly different between patients with and without bacteremia. Conclusions: We found a low rate of bacteremia in patients admitted with confirmed SARS‐CoV‐2 infection. In hemodynamically stable patients, routine antibiotics may not be warranted in this population.